PENGARUH KUALITAS PELAYANAN BERBASIS E-GOVQUAL DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PENGGUNAAN WEBSITE SILAYAK PADA BKPSDM KOTA PALANGKA RAYA - Rakhel Br Tarigan, Aurelia; Tri Harinie, Luluk; Budiman Bancin, John; Sukmani, Meylinda (Penerbit Lafadz Jaya, 2026)
This study aims to examine the impact of E-GovQual-based service quality and information quality on decisions in using the Silayak website at the Palangka Raya City Human Resources Development and Personnel Agency (BKPSDM). The method used was a quantitative associative approach, involving a sample of 74 respondents, consisting of Civil Servants (ASN) as active users of the Silayak website, selected using a purposive sampling technique. Data analysis was performed using multiple linear regression using SPSS software. The results indicate that, individually, service quality has a positive and significant influence on the decision to use the Silayak website. Similarly, information quality demonstrated a significant positive influence individually on the decision to use the website, with this variable recognized as a key factor due to its stronger impact than service quality. Together, both variables demonstrated a significant influence on the decision to use the website, with an F-value of 116.512 and a significance level of 0.000. The coefficient of determination (R Square) of 0.766 indicates that the combination of service quality and information quality explains 76.6% of the variation in the decision to use the Silayak website, while the remaining 23.4% is influenced by factors outside this study. This finding emphasizes the importance of system reliability and the delivery of accurate and up-to-date information as vital components in promoting sustainable digital civil service delivery.